2008
DOI: 10.1080/14766080809518707
|View full text |Cite
|
Sign up to set email alerts
|

Self, Soul and Management Learning: Constructing the Genre of the Spiritualized Manager

Abstract: What form of management is suggested by the increased interest in organizational spirituality and what genre of manager does spiritual learning attempt to construct? The growth of interest in organizational spirituality and its implications for management learning and development are discussed. Various approaches for understanding the self are explored, and a model for organizing these approaches, and the ‘Selves’ they imply, are presented. Burgoyne's (2002) outline of the different styles of learning approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, there is a growing critical literature on workplace spirituality (Bell 2008;Lips-Wiersma et al 2009;Mirvis 1997) that points to the dangers of incorporating spirituality into workplace and warns against the use of spirituality as a manipulative tool of organizational control and employee exploitation (Bell and Taylor 2004;Gotsis and Kortezi 2008;Kamoche and Pinnington 2012). Critical scholars underline the dark side of spirituality and warn about the dangers of workplace spirituality being hijacked as a tool of ideological control and manipulation (Case and Gosling 2010;Cullen 2008;Nadesan 1999;Tourish and Pinnington 2002). Brown (2003) stresses that earlier optimism on workplace spirituality has been replaced by greater questioning of its corporate aspect as sceptics consider spirituality as a management fad that repackages organizational change and development initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is a growing critical literature on workplace spirituality (Bell 2008;Lips-Wiersma et al 2009;Mirvis 1997) that points to the dangers of incorporating spirituality into workplace and warns against the use of spirituality as a manipulative tool of organizational control and employee exploitation (Bell and Taylor 2004;Gotsis and Kortezi 2008;Kamoche and Pinnington 2012). Critical scholars underline the dark side of spirituality and warn about the dangers of workplace spirituality being hijacked as a tool of ideological control and manipulation (Case and Gosling 2010;Cullen 2008;Nadesan 1999;Tourish and Pinnington 2002). Brown (2003) stresses that earlier optimism on workplace spirituality has been replaced by greater questioning of its corporate aspect as sceptics consider spirituality as a management fad that repackages organizational change and development initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, business management scholars have reported that the field of management in the corporate sector has been gradually ‘spiritualised’ since the 1990s (Ackers & Preston ). This ‘spiritualisation’ has often been facilitated by human resource development and management training practices (Cullen ), which borrow heavily from ‘new age’ spiritual beliefs (Heelas , Bell & Taylor , Cullen ) that emphasise quests for personal growth and flourishing as opposed to observing the rules of an established faith tradition or religious organisation. Following two decades of such apparent growth (which was evidenced by events such as the establishment of a ‘Management, Spirituality & Religion’ special interest group at the Academy of Management in the late 1990s and the Journal of Management, Spirituality & Religion was first published in 2004), Oswick () undertook a bibliometric analysis of peer‐reviewed research literature on the topic in order to present an empirically based overview of the growth that the field had undergone in order to demonstrate how the newly emerging sub‐field was developing in terms of praxis and scholarship.…”
Section: Introductionmentioning
confidence: 99%
“…The upsurge of interest in spirituality and religion as it applies to the fields of management and organizational studies (Oswick, 2009;Kamoche and Pinnington, 2012) has gradually received increased attention within the field of management development (Bell and Taylor, 2004;Cullen, 2008). Numerous articles, for example, have appeared in the Journal of Management Development on the application of practical wisdom to contemporary management development practices that can be found within certain faith traditions (Meynhardt, 2010;Kletz et al, 2012;Marques, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…"Calling" in contemporary career and management development practice Since Weber (1930Weber ( /1992 defined vocation as a "life task, a definite field in which to work" (p. 39) it has since become variously and confusingly discussed in the much of the research literature (Dik et al, 2009;Dawson, 2005). Substantial work has been undertaken to refine the concept, which has resulted in an understanding of vocation as a something that is simultaneously: meaningful in that provides individuals with a sense of existential purpose (Lips-Wiersma, 2002;Dawson, 2005;Hall and Chandler, 2005); fulfilling for the individual who commits to a vocation, principally through helping others or creating social value (Hall and Chandler, 2005;Lips-Wiersma and McMorland, 2006), and: appeals to the individuals need for a coherent, directed sense of inner, authentic selfhood (Heelas, 1996;Cullen, 2008). Wrzesniewski et al (1997) usefully elaborate on Bellah's (1985) distinction between jobs, careers and callings by defining jobs are work relationships which are solely based on material benefits, careers are based on advancement through occupational structures, and callings as work positions as inseparable from the individual's broader life project.…”
Section: Introductionmentioning
confidence: 99%